AMPAkines Target the Nucleus Accumbens to Relieve Postoperative Pain. (November 2016) - Su, Chen; Lin, Hau Yeuh; Yang, Runtao; Xu, Duo; Lee, Michelle; Pawlak, Natalie; Norcini, Monica; Sideris, Alexandra; Recio-Pinto, Esperanza; Huang, Dong; Wang, Jing
Abstract : Background: AMPAkines augment the function of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the brain to increase excitatory outputs. These drugs are known to relieve persistent pain. However, their role in acute pain is unknown. Furthermore, a specific molecular and anatomic target for these novel analgesics remains elusive. Methods: The authors studied the analgesic role of an AMPAkine, CX546, in a rat paw incision (PI) model of acute postoperative pain. The authors measured the effect of AMPAkines on sensory and depressive symptoms of pain using mechanical hypersensitivity and forced swim tests. The authors asked whether AMPA receptors in the nucleus accumbens (NAc), a key node in the brain's reward and pain circuitry, can be a target for AMPAkine analgesia. Results: Systemic administration of CX546 (n = 13), compared with control (n = 13), reduced mechanical hypersensitivity (50% withdrawal threshold of 6.05 ± 1.30 g [mean ± SEM] vs. 0.62 ± 0.13 g), and it reduced depressive features of pain by decreasing immobility on the forced swim test in PI-treated rats (89.0 ± 15.5 vs. 156.7 ± 18.5 s). Meanwhile, CX546 delivered locally into the NAc provided pain-relieving effects in both PI (50% withdrawal threshold of 6.81 ± 1.91 vs. 0.50 ± 0.03 g; control, n = 6; CX546, n = 8) and persistent postoperative pain (spared nerve injury) models (50% withdrawal threshold of 3.85 ± 1.23 vs. 0.45 ± 0.00 g; control, n = 7; CX546, n = 11). Blocking AMPA receptors in the NAc with 2, 3-dihydroxy-6-nitro-7-sulfamoyl-benzo[f]quinoxaline-2, 3-dione inhibited these pain-relieving effects (50% withdrawal threshold of 7.18 ± 1.52 vs. 1.59 ± 0.66 g; n = 8 for PI groups; 10.70 ± 3.45 vs. 1.39 ± 0.88 g; n = 4 for spared nerve injury groups). Conclusions: AMPAkines relieve postoperative pain by acting through AMPA receptors in the NAc. Abstract : Systemic administration of an AMPAkine reduced pain and depression behavior. AMPAkine administration directly into the nucleus accumbens similarly reduced acute pain. The data suggest AMPAkines are novel analgesics for postoperative pain whose effect is mediated in part by activity in the nucleus accumbens.